Dynamic neural networks for process modelling in fault detection and isolation systems - Korbicz, Józef (1951- ); Patan, Krzysztof; Obuchowicz, Andrzej (Zielona Góra: Uniwersytet Zielonogórski)
A fault diagnosis scheme for unknown nonlinear dynamic systems with modules of residual generation and residual evaluation is considered. Main emphasis is placed upon designing a bank of neural networks with dynamic neurons that model a system diagnosed at normal and faulty operating points.
Keywords: fault detection; dynamic neural networks; non-linear modelling; learning algorithms; FL-classifier; two-tank system